Korelasi Nilai SPAD dengan Intensitas Serangan Penyakit Blas Pada Umur Padi Yang Berbeda - Sudiarta, I Made; Wijaya, I Made Anom Sutrisna; Sulastri, Ni Nyoman (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2024)
Tanaman padi (Oryza sativa L.) merupakan tanaman pangan penting yang telah menjadi makanan pokok lebih dari setengah penduduk dunia. Padi sawah yaitu tanaman padi yang dalam pertumbuhannya memerlukan air. Ketidakpastian di masa depan terkait ketersediaan pangan menimbulkan rasa khawatir berbagai pihak karena berbagai tantangan yang ada. Tantangannya antara lain bekurangnya luas lahan pertanian yang produktif, masalah iklim, bahaya serangan hama dan penyakit tanaman serta peningkatan degradasi lahan. Tanaman yang sakit adalah tanaman yang tidak dapat melakukan aktifitas fisiologis secara sempurna, yang akan mengakibatkan tidak sempurnanya produksi baik secara kualitas maupun kuantitas. Penyakit blas merupakan salah satu penyakit utama pada pertanaman padi yang disebabkan oleh cendawan Pyricularia oryzae Cav. Penelitian ini bertujuan untuk menegetahui hubungan kandungan klorofil dengan intetnsitas serangan penyakit blas pada umur padi yang berbeda. Abstract Rice is an important food crop that has become the staple food for more than half of the world's population. Rice plant health is very important in determining crop yields. The value of chlorophyll has a close relationship with plant health which can determine the yield of rice production. If the health of the plant decreases, it will be susceptible to disease. Blast disease is one of the factors causing plant health to decline. The attack intensity of the disease can be seen in the green on the leaves. SPAD (Soil Plant Analysis Development) is a simple tool that can determine the amount of chlorophyll in plant leaves called SPAD. This study aims (1) to determine the relationship between SPAD and the intensity of blast disease attacks. (2) To obtain a correlation value between SPAD and the intensity of blast disease attacks. Data collection was carried out in Medium Village which is in the Badung Regency area. Sampling data from the age of rice 71 to 94 HST (Day after Planting). To obtain data, 3 rice fields were measured diagonally, 5 points were taken for each rice field plot, 9 clumps were taken for each point, and the SPAD measurement for each clump was divided into 3 parts of the upper, middle, and lower leaf stems. Each leaf is divided into 3 top, middle, and bottom. The intensity can be seen from the distribution of the spots on the leaves. The development of intensity with age and SPAD with age, if the intensity value is high then the SPAD value is low otherwise if the SPAD value is high then the disease attack intensity value is low. From the research results it can be concluded that SPAD with intensity has a linear relationship, with a correlation value of 0.8634 or 86%. Correlated data is very strong because the correlation value exceeds 0.75 or 75%.